Pengaruh Model Problem Based Learning Dan Kecerdasan Siswa Terhadap Hasil Belajar Siswa Kelas XI SMK Ar-Roudhoh Beji Kabupaten Pasuruan - Aliefiyanto Muhammad Richo (Jurnal Penelitian dan Pendidikan IPS, 2022)
Problem in this research is the low of student's study results. Therefore, researcher chose to use a problem-based learning model to determine its effect on student's learning outcomes and examine differences from the model seen from the level of intelligence. Student's learning outcomes problem could occur due to the lack of encouragement and passivity of students in participating in the learning process. In addition, the problem of learning outcome was because students got less grade during daily test. This study aims is to determine the effect of the Problem Based Learning model and the level of student's intelligence on student's learning outcome of class XI SMK Ar-Roudhoh Beji, Pasuruan. The design of this study was a comparative causal experiment with a pretest and posttest control group design consisted of experimental and control classes. The subjects of this study were class XI Multimedia 2 as the experimental class and XI TKJ 1 as the control class. This study used an instrument in the form of a 3-point essay with guidelines for scoring student learning outcomes. The calculation of student's learning outcomes and the level of student's intelligence used a 2x3 factorial. The data analysis technique used SPSS 16.0 for windows. Hypothesis testing was done by using the t-test (partial test). The results of this study indicated that the Problem Based Learning model had an effect on the student's learning in SMK Ar-Roudhoh Beji. The results were evidenced by the class scores which used the Problem Based Learning model that had an average value (85.5) higher than the class which did not use the Problem Based Learning model (79.5). In addition, the difference in the average score of each classification category "A" to category "C", showed a very significant result between the application of the experimental class using the Problem Based Learning model and the control class with the application of the Role Playing model on the basis of student's intelligence at SMK Ar-Roudhoh Beji, Pasuruan. This study concludes that there is an effect of the Problem Based Learning model on student's learning outcomes and there is a difference in the average score of each classification of IQ category "A" to category "C" on learning outcomes based on student's intelligence